Pengelolaan Hutan Kota di Jakarta (Studi Kasus Hutan Kota Srengseng di Jakarta Barat) - Kurniastuti, Agustina Emmi (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
The environmental developpement in Indonesia, especially in Jakarta, is always ignored, which make the environmental quality of Jakarta decreases. The improvement of the environmental quality of Jakarta can be done with a good green space management, especially in the form of urban forest which have a high ecological and social function. We can easily see a bad appearence of the urban forest in Jakarta, including the Urban Forest of Srengseng (UFS). This study was conducted with a qualitative approach. On one hand, the management of UFS can be said as good enough. But on the other hand, this urban forest has not been managed well enough, which is evident from the response of most of the people who complained about the poor condition of the UFS. However, people show a positive support to the existence of the UFS as well as to its management. Therefore, the quality of the UFS needs to be improved by improving several aspects in the management of urban forest, namely the availability of a complete and accurate data about the urban forest and its content, the availability of an adequate technical regulation related to urban forest management, the availability of a long-term planning as a guideline for a sustainable urban forest maintenance, the enhancement of the urban forest management knowledge and skills, and the good cooperation between the urban forest manager and various related parties.